2016
DOI: 10.1103/physreva.94.033806
|View full text |Cite
|
Sign up to set email alerts
|

Triggering filamentation using turbulence

Abstract: We study the triggering of single filaments due to turbulence in the beam path for a laser of power below the filamenting threshold. Turbulence can act as a switch between the beam not filamenting and producing single filaments. This 'positive' effect of turbulence on the filament probability, combined with our observation of off-axis filaments suggests the underlying mechanism is modulation instability caused by transverse perturbations. We hereby experimentally explore the interaction of modulation instabili… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…As a consequence, most of the studies concluded that the wandering of filaments is similar to that of a Gaussian beam (La Fontaine et al 1999, Chin et al 2002, Fujimoto et al 2002, Salame et al 2007, Ma et al 2008, Silaeva et al 2010. On the other hand, filaments are surprisingly robust in air turbulence once they are formed, their onset may be shifted and new filaments can even be nucleated by the modulated refractive index within turbulent cells (Kandidov et al 1999, Ackermann et al 2006b, Salame et al 2007, Houard et al 2008, Paunescu et al 2009, Eeltink et al 2016.…”
Section: Long Distance Filament Propagation and Atmospheric Turbulencementioning
confidence: 99%
“…As a consequence, most of the studies concluded that the wandering of filaments is similar to that of a Gaussian beam (La Fontaine et al 1999, Chin et al 2002, Fujimoto et al 2002, Salame et al 2007, Ma et al 2008, Silaeva et al 2010. On the other hand, filaments are surprisingly robust in air turbulence once they are formed, their onset may be shifted and new filaments can even be nucleated by the modulated refractive index within turbulent cells (Kandidov et al 1999, Ackermann et al 2006b, Salame et al 2007, Houard et al 2008, Paunescu et al 2009, Eeltink et al 2016.…”
Section: Long Distance Filament Propagation and Atmospheric Turbulencementioning
confidence: 99%
“…Wave-front distortions are also expected to perturb the dynamic balance between Kerr self-focusing and plasma defocusing in the filaments. Experimental and theoretical studies were devoted to the influence of air turbulence on filament distance [12,13], filament survival rate [14,15], transverse filament wandering [16,17], filament spectral characteristics [18], optical pulse broadening [19], the enhancement of multifilament generation and filament-induced fluorescence [20,21], triggering filamentation using turbulence [22], and beam shaping that suppresses turbulence [23]. Trivial changes in filamentation have a great impact on sensitivity during remote sensing.…”
Section: Introductionmentioning
confidence: 99%